2013
DOI: 10.1186/1475-9276-12-13
|View full text |Cite
|
Sign up to set email alerts
|

Redistributive effects of the National Health Insurance on physicians in Taiwan: a natural experiment time series study

Abstract: BackgroundPrevious studies have evaluated the effects of various health manpower policies but did not include full consideration of the effect of universal health insurance on physician re-distribution. This study examines the effects of implementing National Health Insurance (NHI) on the problem of geographic mal-distribution of health providers in Taiwan.MethodsData on health providers and population between 1971 and 2001 are obtained from relevant governmental publications in Taiwan. Gini coefficients deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…While an earlier study in Taiwan demonstrated that implementing NHI had resulted in more equal geographic distributions of physicians, 19 our study revealed that the urban-rural disparity of pediatric healthcare facilities and working hours is still a concern. Nearly half of the towns in Taiwan had no practicing pediatricians.…”
Section: Urban-rural Disparity Of Pediatric Clinicscontrasting
confidence: 59%
“…While an earlier study in Taiwan demonstrated that implementing NHI had resulted in more equal geographic distributions of physicians, 19 our study revealed that the urban-rural disparity of pediatric healthcare facilities and working hours is still a concern. Nearly half of the towns in Taiwan had no practicing pediatricians.…”
Section: Urban-rural Disparity Of Pediatric Clinicscontrasting
confidence: 59%
“…However, in multivariate analysis this characteristic showed no association with remote practice, and thus did not affect interpretation of the results. Finally, this study did not adjust for other predictors of rural preference found in other studies such as job-related factors (i.e., quality of relationships with colleagues, access to specialist consultations, health facility infrastructure and equipment) ( 79 – 81 ), and locational factors (i.e., access to transportation, socioeconomic development, population density, and health insurance coverage) ( 82 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing use of TCM is somewhat related to the growth of the number of TCM physicians in Taiwan [ 17 ]. A previous investigation reported that the density of TCM increased from 1.39 physicians per 10,000 residents in 1996 to 1.78 physicians per 10,000 residents in 2001 [ 27 ]. Our results also showed that the prevalence of acupuncture use in stroke patients increased with the increasing density of TCM physicians.…”
Section: Discussionmentioning
confidence: 99%